A hard rock of age - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
In most ACP countries the proportion of old people will grow for decades yet, despite HIV/AIDS and other ills. The average age of a cocoa farmer in Ghana is 56. Is agriculture going grey?What were those seven ages of man again, those passages from...